Comparison of Different Swabs for Sampling Inorganic Gunshot Residue from Gunshot Wounds: Applicability and Reliability for the Determination of Firing Distance. Issue 2 (5th July 2018) - Merli, Daniele; Amadasi, Alberto; Mazzarelli, Debora; Cappella, Annalisa; Castoldi, Elisa; Ripa, Stefano; Cucca, Lucia; Cattaneo, Cristina; Profumo, Antonella
Abstract: This study concentrates on samples of bare pork skin, with and without bristles, and dried bovine ribs shot with a semi‐automatic pistol to find the best methodology and sampling surface in the search for inorganic gunshot residues (IGSR). Four quadrants of known surface areas were sampled at different distances from the bullet's hole with different swabs: tapes in graphite, Leukosilk® white tape, 3M® transparent tape, and a cotton swab to assess the technique able to collect the highest amounts of IGSR with the lowest contribution of the blank. The cotton swab wet in 10% HNO3 gave the best results. The highest amounts of IGSR, measured by ICP‐OES and MS, were detected on a surface of 3‐cm radius from the bullet's edge. The amount of metals collected decreased with the firing distance between 20 and 60 cm. The procedure was efficient for sampling different tissues like skin and bones.